HUBUNGAN RELATIONSHIP MARKETING DENGAN CUSTOMER LOYALTY PADA TERMINAL PHOTO SUPPLY PEKANBARU - Kurniawan, Teuku Reza (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : This research was conducted at Pekanbaru Photo Supply Terminal. This research was conducted proposal seminar. The population of this research is a customer in 2019 amounting to 68 people. Because the population is small, all populations are sampled or called total sampling techniques. So the sample in this study was 68 customers of Pekanbaru Photo Supply Terminal. Data analysis in this study uses descriptive quantitative method. Based on the results of data processing obtained that hypothesis testingwith t test there is a t count of 8.134meanst calculate = 8.134 >ttable= 1.66827 which means there is a significant influence between relationshipmarketing variableson Costumer Loyalty Terminal Photo Supply Pekanbaru. And based on linear regression equation there is a significant influence between RelationshipMarketing variableson Costumer Loyalty Terminal Photo Supply Pekanbaru. indicated by the determinant coefficient (R Square) value of 0.501 this means that relationshipmarketing's influenceon Costumer Loyalty is 50.1% while the rest is (100% - 50.1 = 49.9 %) influenced by other variables outside of this RelationshipMarketing variable.